Market Power in Emission Permit Markets: Theory and Evidence - Beat Hintermann (Center for Economic Studies and ifo Institute (CESifo), 2013)
A well-known result about market power in emission permit markets is that efficiency can be achieved by full free allocation to the dominant firm. I show that this result breaks down when taking the interaction between input and output markets into account, even if the firm perceives market power in the permit market alone. In fact, the dominant firm may have an incentive to inflate the permit price even if it receives no free permits at all. I examine the empirical evidence for price manipulation by large electricity firms during Phase I of the EU ETS. I find that the pattern and extent of firms' allowance holdings are consistent with strategic price manipulation, and they appear unlikely to be the result of precautionary purchases due to carbon risk.
Keywords: H32; Q48; Q53; Q54; Q58; 330; emission permit market; market power; cost pass-through; price manipulation